PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SUMBER INDAH LESTARI (Dan+Dan) WILAYAH KOTA DEPOK - Pitaloka, Fajar; Dameria Angelina2, Stephanie (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
The purpose of this study is to determine and analyze the effect of Compensation and Work Discipline on Employee Performance in Depok city. The type of research used is explanatory research with research methods in the form of data collection using questionnaires. The data analysis model used is multiple linear regression analysis. Sample selection is done by quota sampling. The sample amounted to 41 respondents, using multiple linear regression analysis.The regression test results showed that 43.3% of employee performance factors could be explained by compensation and work discipline, while the remaining 56.7% were explained by other factors not studied in this study. While the results of the F test show that simultaneously the compensation variable and the work discipline variable simultaneously have a positive and significant effect on employee performance with the results of the analysis, namely the calculated F value = 16.276 > from Ftable = 3.240. The results of the t test show that the Work Discipline variable shows the results of the analysis t count (4.985) where ttable (2.022 () then, partially the variable has a positive and significant effect on the Performance of store employees and + and the Depok city area. The Compensation variable does not have a positive and significant effect on the Performance of Store Employees and + And Depok City Area with the value of the analysis results t count (1.574) where ttable (2.022) (. The dominant variable that affects the performance of store employees and + and the Depok city area is Work Discipline.